O primeiro Curso de Economia Rural Doméstica na Paraíba: Bananeiras (1950-1959) - Santos, Wanderléia Farias (2019)
ABSTRACT The present work has the objective of constructing a historical narrative of the first Course of Domestic Rural Economy of Paraíba, located in the city of Bananeiras/PB (1950-1959). For this, a qualitative research was developed guided by the assumptions of the New Cultural History, taking as sources three manuals of Domestic Economics, as well as several other documents, such as class diaries, work plans, Official Diary and photographs, with the intention to understand the school culture of the course in Bananeiras, reconstituting its history. The theoretical framework chosen was Chartier (1990), with the concept of representation, practices and appropriation; Certeau (1994) with the discussion about the practices, strategies, appropriations and tactics of daily life; Julia (2001), with the understanding of the concept of school culture; Frago and Escolano (2001), with the concept of school space as a place of subjectivities; Berman (1986), with the concept of conservative modernization, Pinsky (2012), historicizing the social place of women in the Golden Years, and, Burke (2005), with the understanding of New Cultural History. It was understood that the Course of Domestic Rural Economy in Bananeiras, spreaded modern/conservative education, because it defended an educational model that accompanied the developmental process of the country, but at the same time, propagated an education based on family base principles, focused on the moral values, of discipline, control and domination of the predominant social group of the time. The course did not emancipate women; it was not its intention. Household economics manuals clearly show this power relationship when they explicitly state that a woman's place is at "home". The women who attended the course (teachers and students) appropriated this speech "naturally". In this sense, apparently harmless, the manuals were cultural devices that educated, controlled and defined ways of being and acting of their readers.